Gene expression profiling reveals underlying molecular mechanism of hepatoprotective effect of Phyllanthus niruri on thioacetamide-induced hepatotoxicity in Sprague Dawley rats - Amin, Z.A.; Alshawsh, M.A.; Kassim, M.; Abdulla, Mahmood Ameen; Ali, H.M. (BioMed Central, 2013)
Background: The liver plays an essential role in the body by regulating several important metabolic functions. Liver injury is associated with the distortion of these functions causing many health problems. Pharmaceutical drugs treat liver disorders but cause further damage to it. Hence, herbal drugs are used worldwide and are becoming increasingly popular. Methods: The hepatoprotective activity of Phyllanthus niruri (PN) was evaluated against liver cirrhosis induced by thioacetamide (TAA) in male Sprague Dawley rats. Rats received intraperitoneal injections of thioacetamide (TAA, 200 mg/kg, b.w. three times weekly) for eight weeks. Daily treatments with plant extract (200 mg/kg) were administered orally for eight weeks. At the end of the study, hepatic damage was evaluated by monitoring transforming growth factor (TGFβ), collagen α1 (Collα1), matrix metalloproteinase-2 (MMP2) and tissue inhibitor of matrix metalloproteinase-1 (TIMP1) gene expression by real-time PCR. Moreover, different chromatographic techniques including column chromatography, thin layer chromatography, and Ultra Performance Liquid Chromatography (UPLC) with Liquid Chromatography/Mass Spectrometry (LC/MS) were used to isolate the active constituents of the plant. Results: The results revealed that treatment with PN significantly reduced the effect of thioacetamide toxicity and exhibited effective hepatoprotective activity. The mechanism of the hepatoprotective effect of PN is proposed to be by normalizing ROSs. Additionally, PN treatment regulated the expression of TGFβ, Collα1, MMP2, and TIMP1 genes. In the active fraction of P. niruri, the isolated chemical constituents were 4-O-caffeoylquinic acid and quercetin 3-O-rhamnoside. Conclusions: The results of the present study indicate that PN ethanol extracts possess hepatoprotective activity that is most likely because of the isolated chemical constituents.